ANALISIS KEBERHASILAN FREE THROW PADA ATLET BOLABASKET PUTRA IKOR UNESA DITINJAU DARI SEGI BIOMEKANIKA - Wismanadi, Himawan (Fakultas Ilmu Olahraga, Universitas Negeri Surabaya, 2019)
This research is aims to describe how free throw can be release by IKOR UNESA?s boy basketball team successfully in biomechanics terms. This research method is descriptive analysis. It takes 5 research subjects. This research divided into 2 process which is the first take a data ( videos ) to the subject athletes of basketball and the second is analysis using dartfish software. This study is divided into two processes, namely the first retrieval of data (video) on the subject of IKOR UNESA?s boy basketball team and the second is the analysis using software dartfish. The results showed that the first research subject in the first and second shooting of the ball did not enter the ring because the throw angle was too large and the initial speed was less, whereas. The research subjects of the two male basketball athletes IKOR UNESA in the first and second shooting of the ball did not enter the ring because the throwing angle was too small and the initial speed was lacking. into the ring due to the right throwing angle and the effective maximum height of the ball. The research subject was the fifth male basketball athlete IKOR UNESA, the ball entered the ring on all three shooting experiments carried out, due to the right throw angle and effective maximum ball height.